Effectiveness of Six Sigma Methodology through BSC in Banking Industry - Nayeri, Mahmoud Dehghan; Rostami, Malihe (Journal of Asian Business Strategy, 2016)
This paper aims to discuss the effectiveness of Six Sigma through balanced scorecard in banking industry. Six Sigma is a powerful analytical technique which yields a dramatic reduction in defects, errors, or mistakes in production and service processes. So it can be useful to find defectives in financial institutions and banks while it can accompany with BSC to approach all organization aspects. Reaching this aim, this paper tries to survey the effectiveness of Six Sigma through balanced scorecard aspects in one of Iranian pioneer banks in deploying aforementioned methodologies. Respondents have been extracted among bank experts with various backgrounds who experienced both techniques in practice for at least four continues years. Findings depict that customer aspect is the most appropriate aspect for implementing Six Sigma, while Learning; Financial and Internal process aspects are less suitable respectively. It is fruitful to declare that all BSC aspects are prone to use the advantages of Six Sigma in practice according to respondent’s points of view.